Islamic Criminal Jurisprudence on the Offence of Trafficking in Persons: An Interpretation of Fasād fī al Arḍ and Ḥadd Offence - Muhammad Sohail; Ataullah Khan Mahmood (Pakistan Journal of Islamic Research)
Divine law is the basic law in the Muslim states that guides the positive law of the state. Islamic law is called the Sharī’ah; while Islamic jurisprudence is called the Fiqh. Allāh Almighty has prescribed fixed punishments for some offences. Those offences are called the Hudood offence. There is not any consensus about the exact number of Hudood offences; however the figure fluctuates from four to ten offences that fall in the category of Hudood offences. Islamic criminal jurisprudence developed in the fact that trafficking in persons is included in the category of Hudood offences. Allāh almighty has prescribed limits for every act of human being. Any person violating such limits is condemned and held as sinful which is called as offence in the positive legal system. Any such violation in more shameful manner is called Fasād fī al Arḍ. Trafficking in persons is also one of the wrongs creating Fasād fī al Arḍ.